2017
DOI: 10.1111/risa.12868
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Hope? How Climate Change News Imagery and Text Influence Audience Emotions and Support for Climate Mitigation Policies

Abstract: Using a national sample, this study experimentally tests the effects of news visuals and texts that emphasize either the causes and impacts of climate change or actions that can be taken to address climate change. We test the effects of variations in text and imagery on discrete emotions (i.e., hope, fear, and anger) and, indirectly, on support for climate mitigation policies. Political ideology is examined as a moderator. The findings indicate that news images and texts that focus on climate-oriented actions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(103 citation statements)
references
References 59 publications
5
96
1
1
Order By: Relevance
“…Converse, 1964), current research on environmental attitudes demonstrate significant left-right cleavages. This research has found that people positioning themselves to the ideological left tend to be more favourable towards environmental protection than those on the ideological right (Feldman & Hart, 2017;Greenhill, Leviston, Leonard, & Walker, 2014;Hamilton & Saito, 2015;Liu, Vedlitz, & Shi, 2014;McCright & Dunlap, 2013), and that this ideological cleavage is even growing larger over time (McCright, Xiao, & Dunlap, 2014;Smith & Leiserowitz, 2012). In part, the left-right differences in policy attitudes are suggested to be a result of the ideological right's desire to limit governmental interference (Milbrath, 1986), protect free-market capitalism (Campbell & Kay, 2014) and preserve the current economic and political system (Feygina, Jost, & Goldsmith, 2010;Häkkinen & Akrami, 2014).…”
Section: The Effects Of Compensatory Schemes and Ideological Constraintsmentioning
confidence: 81%
See 2 more Smart Citations
“…Converse, 1964), current research on environmental attitudes demonstrate significant left-right cleavages. This research has found that people positioning themselves to the ideological left tend to be more favourable towards environmental protection than those on the ideological right (Feldman & Hart, 2017;Greenhill, Leviston, Leonard, & Walker, 2014;Hamilton & Saito, 2015;Liu, Vedlitz, & Shi, 2014;McCright & Dunlap, 2013), and that this ideological cleavage is even growing larger over time (McCright, Xiao, & Dunlap, 2014;Smith & Leiserowitz, 2012). In part, the left-right differences in policy attitudes are suggested to be a result of the ideological right's desire to limit governmental interference (Milbrath, 1986), protect free-market capitalism (Campbell & Kay, 2014) and preserve the current economic and political system (Feygina, Jost, & Goldsmith, 2010;Häkkinen & Akrami, 2014).…”
Section: The Effects Of Compensatory Schemes and Ideological Constraintsmentioning
confidence: 81%
“…Drews & van den Bergh, 2016). In an American context, both Feldman and Hart (2017), as well as Shwom, Bidwell, Dan, and Dietz (2010), contend that public support is key for motivating politicians to take climate action. Finally, Rabe and Borick (2012; see also Löfgren & Nordblom, 2009) point to the importance of reframing carbon pricing measures as neither a 'tax', nor on 'carbon', in response to unfavourable mass opinion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Se ha señalado que diferentes enfoques y encuadres pueden hacer variar los efectos de los mensajes sobre cambio climático (Bilandzic, Kalch, & Soentgen, 2017;Feldman & Hart, 2018) y que estas diferencias en el tratamiento de la noticia pueden provocar efectos distintos en las actitudes e intenciones de los usuarios . Así, puesto que los usuarios reaccionan de manera diferente ante distintos encuadres (Lee, Chang, & Chen, 2017) es necesario que estudios posteriores comparen las respuestas de los participantes ante varios estímulos que incluyan distintos enfoques.…”
Section: Limitaciones Y Prospectivaunclassified
“…Finally, we argue for a greater scientific understanding of narrative 'medicine' and mindsets at the larger scale. Scientists and other scholars are already in deep discussions on the importance of narrative as a means to effectively communicate the causes and consequences of climate change [9][10][11][12], or in the case of infectious disease, the value of narrative in encouraging vaccine uptake [13,14]. Our focus here is largely on NCDs.…”
Section: Roadmap To the Viewpointmentioning
confidence: 99%